Giant cell arteritis (Horton’s disease): report of 18 cases. - Cunha, R M; Horta, A B; Goes, M J; Castro, A S (Acta Médica Portuguesa, 1993)
The authors present and comment on 18 cases of Giant-cell arteritis observed in an Internal Medicine Department between 1984 and 1991 with emphasis on clinical aspects and diagnostic considerations, on the occult presentation forms and, finally, on two cases with peripheral neuropathy. The clinical manifestations were: headache (78%), general non-specific symptoms (78%), polymyalgia rheumatica (61%), sudden blindness (33%), local temporal signs (28%), jaw pain (24%), articular complaints (17%) and peripheral neuropathy (12%).